2013
DOI: 10.1007/s00228-012-1463-7
|View full text |Cite
|
Sign up to set email alerts
|

The case of drug causation of childhood asthma: antibiotics and paracetamol

Abstract: AimThe rising prevalence of bronchial asthma has led to world-wide efforts to understand and stem this development. Cross-sectional studies appear to show that early childhood use of antibiotics may be an important contributory factor, with paracetamol as an additional suspected cause. However, mounting evidence, which is reviewed here, points to various confounding factors as the major reasons for these reported associations.MethodsPubMed and EMBASE were systematically searched for studies on associations bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 89 publications
1
46
0
Order By: Relevance
“…Retrospective studies have reported antibiotic treatment in early life to be associated with increased risk of asthma, although the results may still be influenced by reverse causation or confounding by indication 42 .…”
Section: West 11mentioning
confidence: 99%
“…Retrospective studies have reported antibiotic treatment in early life to be associated with increased risk of asthma, although the results may still be influenced by reverse causation or confounding by indication 42 .…”
Section: West 11mentioning
confidence: 99%
“…An interesting example of this type of bias comes from pediatric studies suggesting that the development of asthma in children <5 years old is associated with the use of antibiotics [111,112]. This association was identified when antibiotics are prescribed for lower respiratory tract infections (LRTI) [113,114]. In this case, the increased risk of asthma could be associated with LTRI, rather than antibiotics.…”
Section: Real Life Studies: Limitationsmentioning
confidence: 99%
“…On the first hand, it is postulated that 'antibiotic-induced growth inhibition of enteric flora can suppress the "education" of Th1 profile immune response in children, leading to the induction of a Th2 allergic inflammatory predisposition' without changes of genome even after exposure to one course of antibiotics in the first year of life [2,12,13,[16][17][18][19][20]. On the other hand, different infectious agents can manipulate the host immunity through induction of Th2/Immunoglobulin (Ig) E response, in order to increase their surviving chances [2,15,21,22].…”
Section: The Role Of Infections In the Respiratory Atopymentioning
confidence: 99%
“…Prevalence antecedent decades [15]. Maybe in a few decades, antibiotics exposure will no longer be a risk factor for asthma and atopy among populations of recently-developed countries, 'including the important period between 0 and 1 year of age' [13]. This concept (in concert with other established risk factors) can explain the increased allergy prevalence in industrialized countries among autochthonous populations, as well as the actual divergent trends in prevalence of respiratory allergies between them and populations of recently-developed countries.…”
Section: Relationship Antibiotics Exposure -At-opy Trendmentioning
confidence: 99%
See 1 more Smart Citation